Recombinant Escherichia coli-driven whole-cell bioconversion for selective 5-Aminopentanol production as a novel bioplastic monomer - Byung Wook Lee; Hee Taek Kim; Hyun Gi Koh; Kyungjae Yu; Gaeul Kim; Yoon Jung Jung; Haeng-Geun Cha; Yunhee Jeong; Yung-Hun Yang; See-Hyoung Park; Kyungmoon Park (Bioresources and Bioprocessing)
Abstract 5-Aminopentanol (5-AP) is a valuable amino alcohol with potential applications in polymer synthesis and bioplastics. Conventional production methods rely on petroleum-based feedstocks and metal catalysts, which raise environmental and sustainability concerns. In this study, a de novo biosynthetic pathway for 5-AP production from l-lysine was developed in Escherichia coli. The engineered pathway consisted of lysine decarboxylase 2 (LdcC), putrescine aminotransferase (PatA), and tested aldehyde reductase (YahK, YihU, YqhD). Among the tested reductases, aldehyde reductase exhibited the highest catalytic efficiency, producing 44.5 ± 2.6 mM of 5-AP (0.44 ± 0.03 mol5 − AP/mol l−lysine). The replacement of the expression system with a T7-based dual-plasmid platform, pET24ma::ldcC, and pCDFDuet-1::yqhD::patA co-transformed into E. coli, increased the production to 60.7 ± 5.8 mM, accompanied by reduced cadaverine accumulation. Further enhancement was achieved by increasing the gene dosage of PatA, leading to 68.5 ± 4.2 mM 5-AP and reduced by 40% in cadaverine levels. Cadaverine is a precursor in the production of 5-AP, and its accumulation is an important factor in the limitation of conversion to 5-AP. Intracellular cofactor regeneration is expected to cause an indirect supply of α-KG, a cofactor, to enhance conversion to 5-AP. To support intracellular cofactor regeneration, glucose supplementation and increased aeration were applied, resulting in a final titer of 78.5 ± 1.2 mM 5-AP and improved precursor utilization. This study is the first report of selective microbial 5-AP production and highlights the importance of PatA expression in pathway optimization. The newly established l-lysine (C6) valorization process which converts l-lysine to high-value materials such as 1,5-PDO, glutarate, and 5-AP offers a promising route for the sustainable biosynthesis of amino alcohols, laying the groundwork for future improvements through enzyme engineering and metabolic design.